ANALYSIS OF TOTAL PLATE COUNT (TPC) OF GERMS ON WALLS AND FLOORS OFTREATMENT ROOM BASED ON HOSPITAL TYPE IN EAST JAVA AND ITS IMPACT ON THE ENVIRONMENT AND HEALTH IN 2019 - Khanifah, Akhmad Abu (International Journal of Psychosocial Rehabilitation, 2020)
Hospitals, aside from being a health service facility, can also be a place for transmission of infectious diseases that can affect health problems. One sign of transmission of nosocomial infection is high number of germs on the walls and floors in treatment room. This can result in transmission of nosocomial infections by patients, medical and non-medical staffs and visitors from the treatment room.To analyze the total plate count (TPC) of germs on the walls and floors of treatment room by hospital type in East Java and its impact on the environment and health in 2019 This type of research was a quantitative study with cross sectional design, using data from the test of the total number of germs on the walls and floors of hospital treatment room by BBTKLPP Surabaya. The data were processed with statistical techniques and analyzed by descriptive and cross tabulation (crosstab The TPC requirements for walls and floors germs according to the regulations is 5-10 CFU/cm2 . The results showed total number of germs on the walls and floors in the treatment room as many as 83.3% of hospitals fulfilled the requirements and as many as 16.7% of the hospitals did not.Type B and C hospitalsthat did not fulfilled the requirements, 16,67% type B and 28.57% of type C. TPC germs on the walls and the floors of treatmentroom that didnt fulfilled the requirements, the highest, were in hospitals with type C. After analysis, there was a weak relationship between the TPC of germs on the walls and floorsand hospital type (coefficient contingency = 0.2 58), which meantthat a good type of hospital didnot guarantee a small TPC of germs. The total plate count of germs on floors and walls of patient treatment rooms in hospitals throughout East Java the majority were still below the standard quality in accordance with the Regulation of Health Minister RI Number 7 Year 2019 concerning Hospital Environmental Health which is equal to 5-10 CFU/cm2. But there were still some who over the standard quality that has been set, so the manager of the hospital should be more supervising in terms of hygiene and sanitation in the treatment room.